2002
DOI: 10.1177/027836402321261896
|View full text |Cite
|
Sign up to set email alerts
|

Nonholonomic Motion Planning for Coupled Planar Rigid Bodies with Passive Revolute Joints

Abstract: Motion planning for coupled rigid bodies in a horizontal plane is investigated. The rigid bodies are serially connected by passive revolute joints. The dynamic constraints on the system are second-order nonholonomic constraints. We attempted to control those n coupled rigid bodies by the translational acceleration inputs at the first joint. If each rigid body is hinged at the center of percussion, it is possible to compose a positioning trajectory by connecting rotational and translational trajectory segments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Under a special hinging assumption, namely that each link has the following passive joint axis located at its center of percussion, it has been shown that the CP position of the last link is a flat output for the system [34]. The sequential planning algorithm of [1] has been extended in [45] to this case, while the flatness approach has been detailed in [22]. We summarize here the results of [22] for the case n = 4, characterizing also potential dynamic singularities that should be avoided at the planning stage.…”
Section: A Planar Robot With Two Passive Jointsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under a special hinging assumption, namely that each link has the following passive joint axis located at its center of percussion, it has been shown that the CP position of the last link is a flat output for the system [34]. The sequential planning algorithm of [1] has been extended in [45] to this case, while the flatness approach has been detailed in [22]. We summarize here the results of [22] for the case n = 4, characterizing also potential dynamic singularities that should be avoided at the planning stage.…”
Section: A Planar Robot With Two Passive Jointsmentioning
confidence: 99%
“…The degree of underactuation is thus equal to two. It is assumed that the fourth link is hinged exactly at the center of percussion (CP 3 ) of the third link, which is the same special condition used in [34,45].…”
Section: Dynamic Model and Partial Feedback Linearizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. De Luca [16] 2009 Roy and Asada [27] wing box…”
unclassified